Proliposomes as prolonged intranasal drug delivery systems - Jung, BH; Chung, SJ; Shim, CK (EDITIONS SANTE, 2002)
Proliposomes are defined as dry, free-flowing granules that form a liposomal dispersion on contact with water. In the present review, the feasibility of using proliposomes as drug delivery systems for intranasal administration was investigated. By applying drug-loaded proliposomes to the nasal cavity of rats, fairly rapid and prolonged delivery of propranolol and nicotine to the systemic circulation could be achieved. This rapid absorption can be attributed to the immediate release of drugs from the surface of the proliposomes, while prolonged delivery can be attributed to the sustained release of drugs from the liposomes that were reconstituted from proliposomes on contact with nasal fluid in the nasal cavity. As the result, the mean residence time (MRT) of the drugs in the systemic plasma of rats could be substantially extended compared to cases where the drugs were administered in the form of aqueous solutions via the nasal route. In addition, proliposomes have a number of advantages over liposomes. For example, they tolerate sterilization by ultraviolet and gamma-rays, and are much more stable physicochemically. These collective advantages suggest that proliposomes have considerable potential for achieving a prolonged delivery of drugs via the nasal route.
Keywords: LOADED NEUTRAL PROLIPOSOMES; NASAL ABSORPTION; NICOTINE DELIVERY; TRANSDERMAL NICOTINE; PHARMACOKINETICS; PROPRANOLOL; PHOSPHATIDYLCHOLINE; HYDROLYSIS; ADRIAMYCIN; CLEARANCE